Fasciolopsis buski infection of the biliary tract: a case report - Shuai Luo; Xiaoxue Tian; Ting Xu; Jinjing Wang (Diagnostic Pathology)
Abstract Background Fasciolopsis buski is a large fluke that parasitises the human small intestine, with its infection in the biliary tract being even rarer. Given its relatively rare occurrence in recent years, the clinical diagnosis of F. buski infections can pose certain challenges. Case demonstration A 59-year-old male patient with a history of consuming raw pig blood was admitted with recurrent upper abdominal pain for over 10 years. Hepatobiliary and pancreatic magnetic resonance cholangiopancreatography showed stenosis of the lower end of the common bile duct, dilatation of the intrahepatic and extrahepatic bile ducts above, and tortuous strips in the common bile duct, indicating parasitic infection. Histopathological examination further confirmed a diagnosis of parasitic infection with F. buski in the biliary tract. The patient was treated with praziquantel after surgery and did not exhibit recurrence during 6 months of follow-up. Conclusions Biliary tract infection with F. buski is a rare parasitic disease. This case report discusses an extremely rare case of F. buski infection of the biliary tract caused by consuming raw pig blood. The clinical features, common diagnostic methods, imaging and pathological features, differential diagnosis, treatment, and prognosis of this disease were reviewed to facilitate an improved understanding of this rare condition.